h= nb/ b+nt for "b" I have no idea where to even begin.
P Panama New member Joined Nov 29, 2008 Messages 29 Nov 29, 2008 #1 h= nb/ b+nt for "b" I have no idea where to even begin.
F fasteddie65 Full Member Joined Nov 1, 2008 Messages 360 Nov 29, 2008 #2 Solve; h = nb/(b + nt) for "b" I added parentheses. h = nb/(b + nt) h(b + nt) = nb hb + hnt = nb hb - nb = -hnt nb - hb = hnt b(n - h) = hnt b = hnt/(n - h)
Solve; h = nb/(b + nt) for "b" I added parentheses. h = nb/(b + nt) h(b + nt) = nb hb + hnt = nb hb - nb = -hnt nb - hb = hnt b(n - h) = hnt b = hnt/(n - h)
D Denis Senior Member Joined Feb 17, 2004 Messages 1,707 Nov 29, 2008 #3 h = nb / (b + nt) ; cross multiply: nb = hb + hnt nb - hb = hnt b(n - h) = hnt b = hnt / (n - h) You said: "I have no idea where to even begin." WHY? Bad teacher? Miss classes?
h = nb / (b + nt) ; cross multiply: nb = hb + hnt nb - hb = hnt b(n - h) = hnt b = hnt / (n - h) You said: "I have no idea where to even begin." WHY? Bad teacher? Miss classes?